The tourism industry and its role in sustainable, inclusive development - T. V. Yurieva (Путеводитель предпринимателя)
The strategy for the development of the tourism industry is considered, focused both on overcoming the crisis situation that has arisen as a result of the pandemic and on achieving the goals of sustainable, inclusive development in the post–crisis period. The strategy includes such stages as crisis management, financial recovery and post–crisis development, implemented through special regulatory instruments based on the interaction of the state, private sector and society. Practical recommendations have been developed to improve the efficiency of this strategy in the modern Russian economy.